Gaya pembelajaran KOLB terhadap pencapaian Matematik dalam kalangan murid orang asli - Chuthamar Suwanmani, Asian (2024)
The learning style employed by the Orang Asli pupils play an important role in determining their learning patterns in classroom. By employing suitable learning styles for the Orang Asli pupils, this approach may improve their understanding in Mathematics. This study aims to examine the Kolb Learning Styles practiced by the male and female Orang Asli pupils, and its impact on their Mathematics performance based on gender. This study employed a quantitative approach which consisted of a sample of 76 Year Six Orang Asli pupils at five primary schools in the district of Sungai Siput, Perak. This study used stratified sampling to select a total of 76 from a total population of 160 Orang Asli pupils. Two instruments, namely the Kolb KLSI- 3.1 learning style questionnaire, which contained 40 items, and a mathematics test, which included 20 items, have been adopted for this study. Descriptive statistics and a one-way ANOVA tested to analyze the collected data and determine the difference between the means of more than two groups' Kolb Learning Styles. The findings showed that there was no significant difference in the mathematics performance between male and female Orang Asli pupils. Furthermore, this study found that most male pupils adopted the assimilation learning style, that is, solving mathematical problems based on riddle. On the other hand, most female pupils adopted the divergent learning style. The implication of this study practically can be used as a guide for Malaysian Mathematics teachers to evaluate traditional teaching and learning methods in Mathematics and encourage the development of inclusive pedagogical strategies that meet the appropriate learning styles among Orang Asli pupils. Future studies can be directed toward case study research which involve qualitative data that can explain the learning style of Orang Asli pupils in Mathematic.